Confocal Microscopy and Anterior Segment Optical Coherence Tomography Imaging of the Ocular Surface and Bleb Morphology in Medically and Surgically Treated Glaucoma Patients: A Review - Carmela Carnevale; Ivano Riva; Gloria Roberti; Manuele Michelessi; Lucia Tanga; Alice C. Verticchio Vercellin; Luca Agnifili; Gianluca Manni; Alon Harris; Luciano Quaranta; Francesco Oddone (MDPI AG, 2021)
Glaucoma patients often suffer from ocular surface disease (OSD) caused by the chronic administration of topical anti-glaucoma medications, especially in cases of long-term therapy with preserved or multiple drugs. Additionally, glaucoma surgery may determine ocular surface changes related to the formation and location of the filtering bleb, the application of anti-mitotic agents, and the post-operative wound-healing processes within the conjunctiva. Recently, several studies have evaluated the role of advanced diagnostic imaging technologies such as in vivo confocal microscopy (IVCM) and anterior segment-optical coherence tomography (AS-OCT) in detecting microscopic and macroscopic features of glaucoma therapy-related OSD. Their clinical applications are still being explored, with recent particular attention paid to analyzing the effects of new drug formulations and of minimally invasive surgical procedures on the ocular surface status. In this review, we summarize the current knowledge about the main changes of the ocular surface identified at IVCM and AS-OCT in glaucoma patients under medical therapy, or after surgical treatment.